1985
DOI: 10.2337/diacare.8.1.s94
|View full text |Cite
|
Sign up to set email alerts
|

Medical Care Patterns at the Onset of Insulin-dependent Diabetes Mellitus: Association with Severity and Subsequent Complications

Abstract: The hospitalization of a child at the onset of insulin-dependent diabetes mellitus (IDDM) has become routine in many parts of the world, although controversy exists about its necessity. We examined the patterns of medical care use and the prognosis for acute complications after diagnosis for children with newly diagnosed IDDM in Colorado from 1978 to 1982. We reasoned that if children cared for entirely in outpatient settings at diagnosis had no more frequent acute complications after diagnosis than hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 6 publications
2
16
2
Order By: Relevance
“…The proportion of patients admitted at diagnosis varied from 48-100 % between districts, and two of the eight districts accounted for 48 % of all those not admitted. Our study confirmed that admission at diagnosis does not affect subsequent outcome measures such as readmission or episodes of severe hypoglycaemia, even when the groups were matched for severity of disease at presentation [6,15]. A survey of British paediatricians found that 87 % admitted more than 80 % of all new cases, but that 47 % would change this policy if better community facilities became available [16].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The proportion of patients admitted at diagnosis varied from 48-100 % between districts, and two of the eight districts accounted for 48 % of all those not admitted. Our study confirmed that admission at diagnosis does not affect subsequent outcome measures such as readmission or episodes of severe hypoglycaemia, even when the groups were matched for severity of disease at presentation [6,15]. A survey of British paediatricians found that 87 % admitted more than 80 % of all new cases, but that 47 % would change this policy if better community facilities became available [16].…”
Section: Discussionsupporting
confidence: 70%
“…Girls are more likely to be readmitted than boys but the relationship with age at diagnosis is inconsistent. We found younger children to be at highest risk whereas Haman et al [6] found the risk highest in adolescence, and Hardie et al [3] found no relationship with age.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…It is conceivable that structured education in the first course after diabetes onset results in lower complication events and will lead to lower hospitalization in the following [17,29,30,31,32,33]. Nevertheless, it has to be discussed whether educational programmes can be performed in outpatient settings.…”
Section: Discussionmentioning
confidence: 99%
“…Although no similar information exists for U.S. Hispanics, these race differences are presumably due in large part to differences in socioeconomic conditions. In Colorado, the rate of rehospitalization among Hispanic IDDM patients was greater than that among non-Hispanic white patients (22), and those whose mothers had <12 years schooling had twice the risk of rehospitalization than those with mothers who had some college education. These statistics are particularly compelling in light of recent findings that strict attention to diabetes management can cause postponement or avoidance of chronic microvascular complications (23).…”
mentioning
confidence: 92%